2019
DOI: 10.1007/s12098-019-02879-7
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Fat Pattern between Tribal and Non-tribal Girls of Tripura, North-East India

Abstract: Objective To examine the body composition including fat patterning among 744 school going Chakma tribal and non- tribal Bengali girls (366 Chakma tribal and 378 Bengali girls), aged 6-12y from North, Unokoti, Dhalai and South District of Tripura. Methods The subjects were selected using cluster-random sampling method. The anthropometric measurements of height, weight, triceps and subscapular skinfold were recorded. The body mass index (BMI) was also calculated. The meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…However, another recent study found that there were no significant sex differences among Santhal children (FFM: boys-22.2 kg; girls-21.2 kg) of Purulia, West Bengal, and their mean values were lower than the present study(Dutta Chowdhury et al, 2007).The BMI was highly correlated with body composition parameters in both sexes and the magnitude was greater among girls (except in FFMI). Similar results had been earlier reported from Santhals of Purulia (Dutta Chowdhury et al, 2007), Moroccan adolescents(Mehdad et al, 2012), adolescents from Imphal, Manipur(Rajkumari et al, 2012), rural adolescent girls from Kabri Anglong, Assam(Sharma & Mondal, 2018) and Chakmas of Tripura(Saha & Sil, 2019).…”
supporting
confidence: 86%
“…However, another recent study found that there were no significant sex differences among Santhal children (FFM: boys-22.2 kg; girls-21.2 kg) of Purulia, West Bengal, and their mean values were lower than the present study(Dutta Chowdhury et al, 2007).The BMI was highly correlated with body composition parameters in both sexes and the magnitude was greater among girls (except in FFMI). Similar results had been earlier reported from Santhals of Purulia (Dutta Chowdhury et al, 2007), Moroccan adolescents(Mehdad et al, 2012), adolescents from Imphal, Manipur(Rajkumari et al, 2012), rural adolescent girls from Kabri Anglong, Assam(Sharma & Mondal, 2018) and Chakmas of Tripura(Saha & Sil, 2019).…”
supporting
confidence: 86%
“…There is very little data on body composition of tribal girls, though tribals make up around 8.6% of the total population. In the current study by Saha et al, in 6-12 y-old Chakma girls, authors found that girls from the Chakma tribe from Tripura had higher body fat till around 9 y of age, after which they were comparable to non-tribal Bengali girls [2]. Santhal girls had a body fat percentage which was much lower than that of the Chakma girls at all age groups [3], including at 12 y (10.8% in Santhal girls vs. 18.4% in Chakma girls).…”
mentioning
confidence: 44%
“…Body fat tends to increase with age in girls and various factors such as dietary intake, physical activity, pubertal stage and ethnicity influence the body composition. India being a diverse country, body composition of Indian girls is likely to be different in different geographical regions, such as is reported in the current study [2].…”
mentioning
confidence: 75%
“…in 2019 suggested a clear evidence of ethnic variation in fat patterning where Chakma tribal girls showed a greater subcutaneous adiposity in comparison with Bengali girls. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%